Targeting Redox Regulation as a Therapeutic Opportunity against Acute Leukemia: Pro-Oxidant Strategy or Antioxidant Approach? - Alessandro Allegra; Alessandro Tonacci; Laura Giordano; Caterina Musolino; Sebastiano Gangemi (Antioxidants, 2022)
Redox adaptation is essential for human health, as the physiological quantities of non-radical reactive oxygen species operate as the main second messengers to regulate normal redox reactions by controlling several sensors. An abnormal increase reactive oxygen species, called oxidative stress, induces biological injury. For this reason, variations in oxidative stress continue to receive consideration as a possible approach to treat leukemic diseases. However, the intricacy of redox reactions and their effects might be a relevant obstacle; consequently, and alongside approaches aimed at increasing oxidative stress in neoplastic cells, antioxidant strategies have also been suggested for the same purpose. The present review focuses on the molecular processes of anomalous oxidative stress in acute myeloid and acute lymphoblastic leukemias as well as on the oxidative stress-determined pathways implicated in leukemogenic development. Furthermore, we review the effect of chemotherapies on oxidative stress and the possibility that their pharmacological effects might be increased by modifying the intracellular redox equilibrium through a pro-oxidant approach or an antioxidant strategy. Finally, we evaluated the prospect of varying oxidative stress as an efficacious modality to destroy chemoresistant cells using new methodologies. Altering redox conditions may be advantageous for inhibiting genomic variability and the eradication of leukemic clones will promote the treatment of leukemic disease.